Environmental management of sustainable university campuses (2020)
The environmental crisis, pattern of unbridled consumption associated with intensive production model in natural resources usage provokes deep transformations in Nature, as well as the mindset of green thinking and acting, bringing enlightenment to Sustainable Development concept. For instance, the afore mentioned topic becomes the global agenda. This scenario is not apart from universities: this fact does not apply only including environmental subjects in curricula, but also in rethinking campuses daily operations and their adaptation to sustainability parameters. In this sense, the present article aims to discuss the relevance of including the environmental dimension in management action plan on university campuses, pursuing a convergence with main governmental and nongovernmental recommendations. Therefore, this bibliographic research, in qualitative and exploratory basis, intend to present a global environmental state of art towards a Brazilian viewpoint.